What Color Is Your Parachute? 2019: A Practical Manual for Job-Hunters and Career-Changers - Richard N. Bolles (Ten Speed Press, 2018)
In today's complex job-market, the time-tested advice of What Color Is Your Parachute? is needed more than ever. Recent grads facing a changing economic landscape, workers laid off mid-career, and people searching for an inspiring work-life change all look to career guru Richard N. Bolles for support, encouragement, and advice on which job-hunt strategies work—and which don't. This revised edition combines classic elements like the famed Flower Exercise with updated tips on social media and search tactics. Bolles demystifies the entire job-search process, from writing resumes to interviewing to networking, expertly guiding job-hunters toward their dream job.